PROBLEMATIKA DALAM PENEGAKAN HUKUM ATAS PELANGGARAN IZIN MENDIRIKAN BANGUNAN DI SAMARINDA - Sri Indarni (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACTBased on the research that law enforcement against violations of Building Permit implementation by regional rule number 14 year 2002 about Building Permit in the city of Samarinda in that case is by giving advance warning by the Investigators Civil Servant (PPNS) to defendant for cease construction activities for temporary, which after being given a warning if the defendant did not also fulfill a building permit by the Investigators Civil Servant then made an investigation which resulted in the transfer of the file to be solved and decided at the District Court of Samarinda, and the verdict are the trial period of 6 months, jail for 3 months and gets charge case amounted Rp.1000, - (one thousand rupiahs). The law enforcement has been conducted in accordance with what is regulated in regional rule number 14 year 2002 about building permit in the City of Samarinda by the Regional Government of Samarinda. Based on decision of the District Court of Samarinda on that case are imposition of imprisonment for 3 (three) months, which was appropriate and not conflict with what has been regulated in regional rule number 14 year 2002 article 108 paragraph (1),  which the maximum notice of imprisonment imposotion are maximum of 6 (six) months and with that imprisonment imposed also does not conflict with imposing notice one of the sanctions, which have been set out in article 108 paragraph (1) of regional rule about alternative sanctions besides imprisonment is highest penalty of Rp 50.000,- (fifty thousand rupiahs).